Oxygen Transport to Tissue XLI (Springer Nature, 2020)
This book presents cutting-edge papers and perspectives on the transport of oxygen to tissues by scientists in a multitude of disciplines such as biochemistry, engineering, mathematics, medicine, physics, physiology, veterinary and complementary medicine. The book is composed of the following 6 parts: Brain Oxygenation and Function, Tumor Oxygenation and Metabolism, Muscle Oxygenation and Sports Medicine, Cell Metabolism and Tissue Oxygenation, Methodology of O2 Measurements, and Special Topics. The articles in this book have been presented at the 46th annual meeting of the International Society on Oxygen Transport to Tissue (ISOTT 2018) held in Seoul, Republic of Korea, from July 1 to July 5, 2018. Academics, clinical and industry researchers, engineers, as well as graduate students who are interested in oxygen transport to tissue will find this book a great reference and a useful learning resource. The chapters "Near-Infrared Spectroscopy Measured Cerebral Blood Flow from Spontaneous Oxygenation Changes in Neonatal Brain Injury", "Developing a Model to Simulate the Effect of Hypothermia on Cerebral Blood Flow and Metabolism" and "Broadband NIRS Cerebral Evaluation of the Hemodynamic and Oxidative State of Cytochrome-c-Oxidase Responses to +Gz Acceleration in Healthy Volunteers" are available open access under a Creative Commons Attribution 4.0 International License via link.springer.com
English
Keywords: Biomedical engineering; oxygenation; hypoxia; cerebral blood flow; oxygen supply; tissue oximeter